Freeze-Thaw Stability Analysis of the High-Ice Content Soil-Rock Cutting Slope: A Case Study in Oroqen Autonomous Banner, North China - Yuxia Zhao; Jun Feng; Kangqi Liu; Qi Wu; Liqun Wang; Hongyan Liu (Geofluids)
National Highway 332 (referred to as line 332) is the most convenient way for the forest areas (Oroqen Autonomous Banner, etc.) in northern China. This area is located in the high-latitude permafrost regions of the Daxing’anling Mountains. The section of line 332 from Ali River to Kubuchun Forest Farm is 116 km long, and the permafrost section is 7.45 km. Part of the section, K105+700-K105+800, is a road cutting slope with high ice content, and it is also our research object. The slope to be studied is difficult to construct and has high landslide risk, so we arranged thirty-five temperature sensors, four moisture sensors, and eighteen landmarks on the slope to grasp the dynamic changes of the slope under freeze-thaw conditions. After collecting the continuous data of temperature, moisture, settlement, and deformation of the slope, we found that the slope was undergoing freeze-thaw cycles, and the shallow slippage of the slope reached 6.811 cm in 2019. Besides, the drilled core samples were tested in the laboratory and relevant parameters were obtained. Then, the slope stability was numerically simulated in ABAQUS numerical simulation software. After two hundred freeze-thaw cycles, the slope safety factor reached 0.997, indicating that the slope was in a state of extreme equilibrium, so the potential freeze-thaw disasters must be considered during road operation, and higher requirements for the permanent protection of slopes should also be put forward. The study can provide guidance for the design and construction of road cutting slope in the permafrost regions of the Daxing’anling Mountains.